2020
DOI: 10.1007/s00401-020-02152-8
|View full text |Cite
|
Sign up to set email alerts
|

Biological sex and DNA repair deficiency drive Alzheimer’s disease via systemic metabolic remodeling and brain mitochondrial dysfunction

Abstract: Alzheimer's disease (AD) is an incurable neurodegenerative disease that is more prevalent in women. The increased risk of AD in women is not well understood. It is well established that there are sex differences in metabolism and that metabolic alterations are an early component of AD. We utilized a cross-species approach to evaluate conserved metabolic alterations in the serum and brain of human AD subjects, two AD mouse models, a human cell line, and two Caenorhabditis elegans AD strains. We found a mitochon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 90 publications
(117 reference statements)
2
43
0
Order By: Relevance
“…Although Lpl was upregulated across all AD-associated clusters of the hippocampus ( Figures 4 A and 4B), it was visibly upregulated in the CA1-2 and CA3 sublayers of the hippocampus ( Figures 4 C and S8 ). We have previously demonstrated Lpl protein upregulation by western blotting and suggested that it may contribute to altered fat metabolism in our mice ( Demarest et al., 2020 ). Thy1 was also upregulated in the AD strains' CA1 regions and throughout the brain hemisphere.…”
Section: Resultsmentioning
confidence: 75%
“…Although Lpl was upregulated across all AD-associated clusters of the hippocampus ( Figures 4 A and 4B), it was visibly upregulated in the CA1-2 and CA3 sublayers of the hippocampus ( Figures 4 C and S8 ). We have previously demonstrated Lpl protein upregulation by western blotting and suggested that it may contribute to altered fat metabolism in our mice ( Demarest et al., 2020 ). Thy1 was also upregulated in the AD strains' CA1 regions and throughout the brain hemisphere.…”
Section: Resultsmentioning
confidence: 75%
“…The accumulation of G6P can reduce hexokinase activity by competitively inhibiting ATP binding to the active site of the enzyme (Liu et al, 1999). In addition, an unbiased metabolomics approach demonstrated G6P accumulation in humans and mice with AD, which restrains glycolysis (Demarest et al, 2020). Hexokinase binds to the OMM via the voltage-dependent anion channel (VDAC), which controls the mitochondrial permeability transition pore (MPTP) (Harris et al, 2014).…”
Section: Altered Glycolysis In Aging and Admentioning
confidence: 99%
“…A decreased level of GLUT1 and GLUT3 Simpson et al, 1994; The downregulation of hexokinase triggered by the increased G6P competitively binding with hexokinase Decrease the concentration of G6P Increase the activity of hexokinase in order to facilitate glycolysis Liu et al, 1999;Demarest et al, 2020 The inhibition of neuroprotective effects of 2DG caused by an increased concentration of NADH Control the activity of GAPDH Decrease the concentration of NADH and promote 2DG to inhibit the effect of Aβ on neuronal cells Vilalta and Brown, 2014;Kim et al, 2017;Shen et al, 2017 A decreased level of acetyl-CoA Treat with acetyl-L-carnitine which provides additional acetyl-CoA…”
Section: Defective Metabolic Pathways Potential Treatments Outcomes Rmentioning
confidence: 99%
“…DNA repair deficiency is believed to deteriorate the glucose metabolism by driving mitochondrial dysfunction (Demarest et al, 2020 ). Herein, we evaluated the expression levels of three important DNA repair enzymes, MTH1, OGG1/2, and MUTYH (Nakabeppu, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…DNA repair deficiency contributes to mitochondrial dysfunction and deteriorates the glucose metabolism (Demarest et al, 2020 ). MutY homolog (MUTYH), MutT Homolog 1 (MTH1) and Oxoguanine DNA glycosylase 1 and 2 (OGG1/2) are crucial DNA repair enzymes, the oxidative DNA damage can be minimized by the functions of MUTYH with the mispaired bases, MTH1 with oxidized dNTPs and OGG1/2 with the 7,8-dihydro-8-oxoguanine (8oxoG).…”
Section: Introductionmentioning
confidence: 99%